STEREOTYPES OF AFRICAN-AMERICANS REPRESENTED IN LOS SANTOS MISSIONS OF GTA: SAN ANDREAS - Rosyada, Atma Rosyada Sofa (LANTERN (Journal on English Language, Culture and Literature), 2017)
“GTA: San Andreas” is an action adventure video game developed by Rockstar North and published by Rockstar Game. The game’s main storyline represents racial issues in the United States especially the African-American stereotypes. The purpose of  this study is to analyze the gameplay, storyline, and cutscene of the  game. The study uses ergodic, textual, and contextual theories to analyze the data and library research to compile the data. Library research is used to get literary and stereotype theories. There are five stereotypes showed in this game, namely, African-Americans have savage behaviour; African-Americans are poor people who live in ghettos; African-Americans tend to love hip-hop as well as raps music;African-Americans use ebonic language; and African-American males love to wear saggy pants or baggy clothes.